2008
DOI: 10.1111/j.1540-8191.2008.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization of Left Anterior Descending (LAD) Artery with In Situ Left Internal Thoracic Artery (LITA) and Coronary‐Coronary Free LITA Grafts: 12‐Year Patency

Abstract: We used free LITA graft to bypass the distal lesions of LAD in selected patients as a valid alternative to sequential bypass grafting. To the best of our knowledge, this is the only angiographic view of a CCBG in LAD with LITA graft confirming the long-term patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The first coronary-coronary artery bypass was performed in 1987 on a patient with porcelain aorta, the results of which were satisfactory (1, 2, 8, 9). The conduits that are used for coronary-coronary artery bypass are left internal mammary artery, saphenous vein graft, and radial artery (10). Most of the studies showed satisfactory short-and long-term outcomes of coronary-coronary bypass procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The first coronary-coronary artery bypass was performed in 1987 on a patient with porcelain aorta, the results of which were satisfactory (1, 2, 8, 9). The conduits that are used for coronary-coronary artery bypass are left internal mammary artery, saphenous vein graft, and radial artery (10). Most of the studies showed satisfactory short-and long-term outcomes of coronary-coronary bypass procedure.…”
Section: Discussionmentioning
confidence: 99%